Characterization of the complete chloroplast genome sequence of Tinospora sagittata and its phylogenetic implications - Peng, Cuiying (Mitochondrial DNA B Resour, 2019)
Tinospora sagittata is a perennial vine of the family Menispermaceae and distributed in Hunan, Hubei, Guangxi, and Sichuan province of P. R. China. It has been used in Chinese traditional medicine for centuries. The chloroplast (cp) genome of T. sagittata, characterized using Illumina technology, is 163,662 bp in size. There are a total of 130 genes, coding for 85 proteins, 37 tRNAs, and 8 rRNAs. Phylogenetic relationship analysis based on 16 complete cp genome sequences exhibited that T. sagittata was phylogenetically closer to Menispermum dauricum and Stephania japonica.